The diabetes mellitus comorbidity index in European Union member states based on the 2019 European Health Interview Survey - Nóra Kovács; Nour Mahrouseh; Lorenzo Monasta; Angela Andreella; Stefano Campostrini; Orsolya Varga (Scientific Reports)
Abstract Multiple chronic conditions reduce the quality of life and increase healthcare needs for people with diabetes mellitus (DM). This study aims to describe the prevalence of comorbidities associated with DM in the European Union (EU) at national and sub-national levels and to assess the utility of a comorbidity burden index. The study was carried out using microdata from European Health Interview Survey 2019 including adults aged 25 and older with DM from 26 EU member states (n = 20,042). The comorbidity index was calculated for 9 chronic conditions using the self-rated general health of individuals and disability weights obtained from the Global Burden of Disease 2019. Beta regression analysis was performed to evaluate the association between the comorbidity index and several determinants. A higher comorbidity index was found in sub-populations exhibiting lower education, unemployment or other labour status, lower income, rural residence, and poor health behaviours including obesity, physical inactivity, and poor diet. A higher comorbidity burden was observed in Eastern and Southern European countries and specific subregions within each country. The comorbidity index has the potential to identify regions and subpopulations with the highest disability burden and to help develop interventions to improve the quality of life of people with DM.